Transition Metal Phosphides for High Performance Electrochemical Energy Storage Devices - Saleh, Amina (AUC Knowledge Fountain, 2022)
Electrochemical energy storage technologies are nowadays playing a leading role in the global effort to address the energy challenges. A lot of attention has been devoted to designing hybrid devices known as supercapatteries which combine the merits of supercapacitors (high power density) and rechargeable batteries (high energy density). Transition metal phosphides (TMP) are a rising star for supercapattery anode materials thanks to their high conductivity, metalloid characteristics, and kinetic favorability for fast electron transport. Herein, new TMP-based materials were synthesized for use as supercapattery positive electrodes, via a multifaceted approach to yield devices enjoying concurrently high power and energy densities. First, an all-in-one plasma-assisted defect engineering and phosphide conversion of binary metallic nickel cobalt-based hydroxide efficiently increases the capacity, vacancies concentration, effective redox sites, and potential window. Second, controlling the morphology through the relative metallic ratio tunning results in impressively high surface area, large number of active sites, and excellent specific capacity. Combining these strategies yields a device delivering an energy density of 48 Wh kg-1 at a power density of 800 W kg-1, along with an outstanding cycling performance, outperforming most reported NiCo-based materials. The best electrode had a composition of 75% cobalt and 25% nickel. Adding manganese, a third metal, to the defect-engineered and phosphidized system results in superior metrics due to the positive synergism between the three metals at an optimized Mn:Ni:Co ratio. The best electrode had an equimolar composition of the three metals in the electrodeposition solution. Only then the corresponding hybrid device achieves an impressive energy density of 55.25 Wh kg-1 at a power density of 749.91 W kg-1, along with excellent stability. Excitingly, the electrochemical activation (ECA) shows to be an irreplaceable yet overlooked cornerstone. Herein, ECA is examined via a plethora of spectroscopic techniques some of which are novel to the supercapacitors field, such as applying multivariate statistical analyses, besides employing EELS spectrum images. Thanks to the electrochemical optimization approach, a hybrid device is assembled to have superb performance features, exhibiting near-battery energy density: 89 Wh kg-1 at a power density of 848 W kg-1, besides ultrastable performance metrics during 10,000 GCDs. Overall, this study promotes combining synthesis optimizations, electrochemical methods and advanced spectroscopic characterization for a basic understanding of the materials and the rational design of ultrahigh energy density hybrid supercapacitor devices.